Fully Optical in Operando Investigation of Ambient Condition Electrical Switching in MoS2 Nanodevices. Issue 10 (12th January 2023) - Symonowicz, Joanna; Polyushkin, Dmitry; Mueller, Thomas; Di Martino, Giuliana
Abstract: MoS2 nanoswitches have shown superb ultralow switching energies without excessive leakage currents. However, the debate about the origin and volatility of electrical switching is unresolved due to the lack of adequate nanoimaging of devices in operando. Here, three optical techniques are combined to perform the first noninvasive in situ characterization of nanosized MoS2 devices. This study reveals volatile threshold resistive switching due to the intercalation of metallic atoms from electrodes directly between Mo and S atoms, without the assistance of sulfur vacancies. A "semi‐memristive" effect driven by an organic adlayer adjacent to MoS2 is observed, which suggests that nonvolatility can be achieved by careful interface engineering. These findings provide a crucial understanding of nanoprocess in vertically biased MoS2 nanosheets, which opens new routes to conscious engineering and optimization of 2D electronics. Abstract : Atomically thin MoS2 electrical switches are characterized for the first time in operando and in ambient conditions through a non‐invasive spectroscopy‐based method. The study sheds light on the – controversial and still debated – dynamics driving the switching mechanism. It reveals volatile metallic filaments percolating interatomic spacing in MoS2 and stresses the impact of transfer residues on the electrical performance of switches.